Authentic leadership in small businesses: The importance of humility and resilience - Sousa, Marlene (2021)
The main objective of this study is to analyse the impact of authentic leadership on resilience, directly or when mediated by humility, in small and medium-sized enterprises and small businesses since these are personal characteristics that are increasingly determining and differentiating. All over the world, these organisations have been feeling the need to adapt to major societal changes that are taking place at the level of economic, social, political, cultural and ethical relations. The emergence of these new societal conjunctures imposes new conditions on organisations and rebuilds the world of work and business. In this way, authentic leadership and its influence on the behaviour of employees and organisations as a whole are increasingly gaining the attention of academics. This research empirically validates the theoretical arguments that suggest that authentic leadership relates to humility and resilience, both directly and indirectly, and demonstrates that employees are essential resources to help organisations face competitive challenges, take advantage of their employees' potential, and promote organisational efficiency competitive advantages over competitors. The study is based on a questionnaire applied to 109 employees of Portuguese companies, who, in the performance of their professional activity, are in a position of direct subordinates of the top management of these SMEs and small businesses. The analysis of the results obtained allows the conclusion that authentic leaders arouse more humility and more resilience in their subordinates.